Answer:
19
Step-by-step explanation:
by replacing x and y with their given values ,
we get :-
=》2x + 7y - 10
=》(2 × 4) + (7 × 3) - 10
=》8 + 21 - 10
=》29 - 10
=》19
5/9 of chocolate is left because first
You must get like denominator and then subtract, as well as simplify
Answer:
![y=-\frac{1}{2} x +2](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7D%20x%20%2B2)
Step-by-step explanation:
![m=\frac{y2-y1}{x2-x1} = \frac{-2-4}{8-(-4)} =\frac{-6}{12} = -\frac{1}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By2-y1%7D%7Bx2-x1%7D%20%3D%20%5Cfrac%7B-2-4%7D%7B8-%28-4%29%7D%20%3D%5Cfrac%7B-6%7D%7B12%7D%20%3D%20-%5Cfrac%7B1%7D%7B2%7D)
So for a movement along the x-axis left to right by 2 the y-axis drops by 1
This the equation at this point is =
![y=-\frac{1}{2} x+c](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7D%20x%2Bc)
-
Pick any of the two points (x,y) . let's choose ( 8 , -2 )
![y2=-\frac{1}{2} x2+c \\\\..\\\\-2=(-\frac{1}{2} )(8)+c\\-2=-4+c\\\\..\\\\c=2](https://tex.z-dn.net/?f=y2%3D-%5Cfrac%7B1%7D%7B2%7D%20x2%2Bc%20%5C%5C%5C%5C..%5C%5C%5C%5C-2%3D%28-%5Cfrac%7B1%7D%7B2%7D%20%29%288%29%2Bc%5C%5C-2%3D-4%2Bc%5C%5C%5C%5C..%5C%5C%5C%5Cc%3D2)
SO ..
![y=-\frac{1}{2} x+2](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7D%20x%2B2)
So, 5 x (-3) + 7 = -15 + 7 = - 8 , but not 4;
Then, -3 is not a solution to 5x + 7 = 4;